Pemanfaatan Biji Rambutan sebagai Emping Panganan Ringan Antidiabet - Sajaratud Dur; Dahlia Lubis (Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACT. The community service is carried out in Rahuning Village RahuningDistrict Asahan Regency. Rahuning Village has a special characteristic, namely that every house yard has one or the other than rambutan trees. So far, rambutan seeds have not been used but thrown away as waste. The service provides information andinterest in using rambutan seeds to become chips. These rambutan seed chips aresnacks or light snacks that function as antidiabetes. The manufacturing process isrelatively easy. The main process is the crushing/ slab process. This chips can also be varied with the addition of herbs or spices and other mixed ingredients such as tapioca flour, wheat flour, sago, flour, cornstarch , and others. These rambutan seed chips are a light snack as an additional food that functions as an anti-diabetic and provides additional economic value for local residents. Rambutan seeds, which have been categorized as waste, can now be used as a light snack in the form of chips which function as antidiabetes. Keywords: chips, rambutan seeds, antidiabetes.